Comparison of Twin Block appliance and Herbst appliance in the treatment of Class II malocclusion among children: a meta-analysis - Feifei Xu; Ying Fang; Xiaoling Sui; Yapeng Yao (BMC, 2024)
Abstract Background Our meta-analysis aimed to evaluate the efficacy of applying Herbst and Twin Block appliances in the treatment of Class II malocclusion among children. Methods Databases, including PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Infrastructure (CNKI), China VIP Database (VIP), and Wanfang were thoroughly searched from inception to August 9, 2023. The outcomes included skeletal, dental, and soft tissue changes. The weighted mean difference (WMD) was used as the effect indicator, and the effect size was expressed with a 95% confidence interval (CI). The heterogeneity of each outcome effect size was tested, and the heterogeneity statistic I2 ≥ 50% was analyzed by the random-effect model, otherwise, the fixed-effect model was conducted. Sensitivity analysis was performed. Results A total of 12 studies involving 574 patients were included in this meta-analysis. Herbst appliance had a statistically significant increase in mandibular body length (WMD: 1.44, 95% CI: 0.93 to 1.96, P < 0.001) compared with the Twin Block appliance. More increases in angle and distance of L1 to mandibular plane (MP) were found in the Herbst appliance compared with the Twin Block appliance. Significant and greater improvements in molar relationship (WMD: 0.79, 95% CI: 0.28 to 1.29, P = 0.002), posterior facial height (WMD: -1.23, 95% CI: -2.08 to -0.38, P = 0.005), convexity angle (WMD: -1.89, 95% CI: -3.12 to -0.66, P = 0.003), and Sella-Nasion plane angle (U1 to SN) (WMD: 3.34, 95% CI: 2.25 to 4.43, P < 0.001) were achieved in the Twin Block appliance. Herbst and Twin Block appliances produced similar effects in the skeletal and dentoalveolar changes including Sella-Nasion-point A (SNA), Sella-Nasion-point B, point A-Nasion-point B (ANB), overjet, and overbite. Conclusion As the findings revealed both Herbst and Twin Block appliances contributed successfully to the correction of Class II malocclusion. Compared with the Twin Block appliance, the Herbst appliance may have more advantages in mandibular bone movement. Twin Block therapy resulted in more improvement in the aesthetics of the face.